Sistem Pendukung Keputusan Pemilihan Teknisi Terbaik Menggunakan Metode Fuzzy Tsukamoto - Jeperson Hutahaean; Juniar Hutagalung (JURIKOM (Jurnal Riset Komputer), 2022)
One of the Human Resources (HR) management activities carried out is the selection of the best technicians. As is the case with Central Ponsel in determining the best mobile technician. It is not an easy thing to get a qualified HR workforce. The process of selecting technicians is still conventional, all data for new technician candidates is recorded manually, so it takes a long time to process the selection results and is still not accurate. The selection of technicians is based on kinship, resulting in an unobjective assessment and social jealousy for other prospective technicians. This has resulted in the owners of Central Ponsel having difficulty making decisions on choosing the best technician because the process of recapitulating the results of the technician's performance evaluation is done independently and manually, resulting in less accurate assessment results, there is no ranking of the final assessment results so that it is difficult to get the title of the best technician. If allowed to drag on then this can certainly hamper performance and operations which can also cause losses for the owner of Central Ponsel. So to solve the problems mentioned above, you can apply the Fuzzy Tsukamoto method in a Decision Support System (DSS). The purpose of this research is to produce a system that can assist the owner of Central Ponsel in determining the best technician so that they are able to make decisions more effectively and efficiently. Based on the calculation that is declared acceptable is the alternative A-03 with the highest score of 75,625 as the best mobile phone technician. This system is expected to assist in providing recommendations for the best technicians who can be selected to carry out tasks tailored to the needs and conditions.